2017
DOI: 10.1097/pcc.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

Primary Outcome Measures in Pediatric Septic Shock Trials: A Systematic Review*

Abstract: Objective To evaluate all published pediatric randomized controlled trials (RCTs) of patients with septic shock from any cause to examine the outcome measures used, the strengths and limitations of these measurements and whether the trial outcomes met feasibility criteria. Data source We used a previously published database of pediatric critical care RCTs (PICUtrials.net) derived from searches of MEDLINE, EMBASE, LILACS and CENTRAL. Study selection We included RCTs of interventions to children admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…Mortality was the most frequent primary outcome while long-term patient-centred outcomes were rarely used. 4 Systematic review A systematic review will be performed to identify both morbidity and mortality outcomes reported in existing studies involving paediatric sepsis in low-and middleincome countries.…”
Section: Identification Of Existing Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Mortality was the most frequent primary outcome while long-term patient-centred outcomes were rarely used. 4 Systematic review A systematic review will be performed to identify both morbidity and mortality outcomes reported in existing studies involving paediatric sepsis in low-and middleincome countries.…”
Section: Identification Of Existing Knowledgementioning
confidence: 99%
“…7 8 A systematic review into primary outcome measures in paediatric septic shock trials demonstrated that the use of mortality alone had significant limitations and suggested more long-term outcomes should be explored. 4 A standardised way to evaluate trial outcomes is therefore imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Duration of shock and organ dysfunction are two surrogate endpoints that were commonly utilized in the review by Menon et al (5). Although both of these surrogates are associated with mortality in sepsis, it is less clear if reducing duration of shock or organ dysfunction will translate into fewer deaths (11, 12).…”
Section: Are Interventions Valuable Even If They Do Not Decrease Death?mentioning
confidence: 99%
“…In this issue of Pediatric Critical Care Medicine , Menon et al reviewed endpoints used in randomized trials of pediatric septic shock (including Dengue shock) conducted in a pediatric intensive care unit (PICU) and published between 1986 and 2016 in English-language journals (5). The authors determined if primary endpoints met a “feasibility” metric, which they defined as 1) recruitment of at least 90% of the targeted sample size and agreement of the predicted-to-observed outcome rate to within 10% in the control group or 2) finding a statistically significant difference in the primary outcome.…”
mentioning
confidence: 99%
“…Shock in paediatric population is a major problem associated with high mortality and organ failure. 1,2,3 Aggressive and early fluid boluses is the initial treatment of choice. 4,5 Determining intravascular volume status and fluid responsiveness based on clinical examination is challenging.…”
Section: Introductionmentioning
confidence: 99%